ASDSR: An Adaptive Stable DSR Routing Protocol for Mobile Ad-hoc Networks - Natoureah, Hutaf Salah Al-Deen; Karajeh, Huda Abd El-Raheem; Abu Serhan, Alaa' Abd El-Aziz (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Abstract—The process of finding a route between the transmitter and the receiver node in the Mobile Adhoc Networks (MANets) is a renewed issue that is becoming more and more interesting to the researchers as this type of networks grow and expand. The dynamic nature of MANET and the limited capabilities of wireless nodes in terms of memory size and battery charge are the most important obstacles to the routing (path-finding) process between nodes. In this research, we introduced a new protocol based on the well-known DSR protocol to add a mechanism that controls the RREQ Flooding process, which aims to reach more stable (life-long) routes while reducing the overhead of routing process caused by link breakage between nodes and reduce the overhead of network flooding with RREQ messages with each attempt to find a path. In this proposed mechanism, a specific group is selected from within the devices adjacent to the transmitter to be sent RREQ so that these devices are selected based on the stability evaluation criterion. The stability criterion is calculated based on three weighted factors: the speed of the node, the out-degree value (the number of adjacent nodes), and the number of tracks stored in the device memory. The proportion of devices selected is automatically changed adaptively to ensure that the expected throughput of this network is achieved. The proposed protocol was tested using simulation where results showed that ASDSR proved an enhancement in route stability about (0.13), and a decrease in the number of deleted routes by (9%), while maintaining the expected packet delivery ratio of the original DSR by about (0.86).